Scenario-guided policy development in Tanzania - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Tanzanian policy makers came together from 16 to 17 February in Morogoro, Tanzania for a workshop that focused on scenario-guided policy development in the context of climate change to work on Tanzania’s New Environmental Policy. This workshop is part of CCAFS’ PACCA project (Policy Action for Climate Change Adaptation) and was organised in collaboration with the University of Oxford. Photos: E. van de Grift.